Determining the Role of Socio-cultural Factors in Women’s Inclination toward Beauty (Case Study: Tehran) - Naghsh, Amirreza; Vafakhah, Nazila (International Review of Management and Marketing, 2017)
The aim of this study was to determine the role of socio-cultural factors in women’s inclination toward beauty. This study was conducted as a descriptive survey. The population consisted of all women and girls between 15 and 64 years living in the north (districts 1 and 2) and south (districts 19 and 20) of Tehran in 2016. According to Cochran formula, 384 subjects were selected as the sample by multi-stage cluster sampling method. The data were collected by using a researcher-built questionnaire based on the theories of "Albert Bandura", "Erving Goffman" and "Bourdieu" as well as the inclination model to beauty of Pidgan and Russell; its formal validity was approved by a number of respondents and it content validity was confirmed by the supervisor professor and a number of experts in the field of social sciences. The reliability of the questionnaire was calculated using Cronbach’s alpha coefficient as 0.86 and was confirmed. In order to analyze the data, descriptive statistics such as mean, standard deviation and frequencies, analytical and univariate t-tests, MANOVA and Friedman test were conducted. The results of data analysis showed that social and cultural factors play an important role in the inclination of women toward beauty at a significant level (P <0.01). Also, socio-cultural dimensions such as socio-economic status, social acceptance, cultural capital, how to use social media, and group level are significantly related to women’s inclination toward beauty (P <0.01). The results of ranking the cultural-social dimensions showed that social acceptance, socio-economic status, media consumption, social groups and cultural capital respectively have the highest to the lowest ranks in the inclination of women toward beauty. There was no significant difference between the respondents in terms of demographic factors with the exception of differences in opinion between the south and north of Tehran. Keywords: inclination to beauty, women, cultural factors, social factors, Tehran JEL Classification: D91